Prospective biomarker study in newly diagnosed glioblastoma: Cyto-C clinical trial. Issue 1 (24th December 2021) - Griguer, Corinne E; Oliva, Claudia R; Coffey, Christopher S; Cudkowicz, Merit E; Conwit, Robin A; Gudjonsdottir, Anna L; Ecklund, Dixie J; Fedler, Janel K; Neill-Hudson, Tina M; Nabors, Louis B; Benge, Melanie; Hackney, James R; et al.
Abstract: Background: Glioblastoma (GBM) has a 5-year survival rate of 3%-5%. GBM treatment includes maximal resection followed by radiotherapy with concomitant and adjuvant temozolomide (TMZ). Cytochrome C oxidase (CcO) is a mitochondrial enzyme involved in the mechanism of resistance to TMZ. In a prior retrospective trial, CcO activity in GBMs inversely correlated with clinical outcome. The current Cyto-C study was designed to prospectively evaluate and validate the prognostic value of tumor CcO activity in patients with newly diagnosed primary GBM, and compared to the known prognostic value of MGMT promoter methylation status. Methods: This multi-institutional, blinded, prospective biomarker study enrolled 152 patients with newly diagnosed GBM who were to undergo surgical resection and would be candidates for standard of care. The primary end point was overall survival (OS) time, and the secondary end point was progression-free survival (PFS) time. Tumor CcO activity and MGMT promoter methylation status were assayed in a centralized laboratory. Results: OS and PFS did not differ by high or low tumor CcO activity, and the prognostic validity of MGMT promoter methylation was confirmed. Notably, a planned exploratory analysis suggested that the combination of low CcO activity and MGMT promoter methylation in tumors may be predictive of long-term survival. Conclusions: Tumor CcO activity alone was not confirmed as a prognostic marker in GBM patients. However, the combination of low CcO activity and methylated MGMT promoter may reveal a subgroup of GBM patients with improved long-term survival that warrants further evaluation. Our work also demonstrates the importance of performing large, multi-institutional, prospective studies to validate biomarkers. We also discuss lessons learned in assembling such studies.